A Simple Pressurized SOFC Test Rig for Measurements of Cell Performance, Impedance, and Various Overvoltages. (2nd June 2015) - Liang, Jyun-De; Hong, Li-han; Wu, P. C.; Shy, Shenqyang Steven
Abstract : This paper reports a newly designed high-pressure full button cell test platform for measurements of various effects on pressurized solid oxide fuel cells (PSOFC). The testing platform has several parts, from inside out including a specially thread-designed housing carrier for the full button cell, a serpentine heating pipe system for uniform heating of the supplied fuel and air gases, a temperature-controlled furnace, and a large high-pressure vessel together with measuring devices and their associates. Hence, current-voltage curves and AC impedance spectra of any full/half button cells can be conveniently measured. In this study, we present power-generating characteristics and electrochemical impedance spectra (EIS) data of an anode-supported full button cell over a range of pressure ( p = 1~5 atm) at a temperature T = 800 o C. Results show that power densities increase with increasing p at any given current densities. These results are explained by the corresponding EIS data. In addition to the aforesaid power-generating characteristics and EIS results, this study also presents analyses of activation and concentration overvoltages using the Butler-Volmer equation and the related concentration overvoltage equation based on a 1D diffusion model. These overvoltage results will be compared with previous numerical and experimental data to enhance our understanding of the effect of pressurization on the polarization mechanisms in SOFCs.